2022
DOI: 10.1002/trtr.2168
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Questions: A Fellowship of Opportunities for Fostering Preschoolers' Story Comprehension

Abstract: Much attention has been paid to storybook reading as a context for supporting preschoolers' emergent language and literacy. Inferential thinking is essential to listening comprehension and to reading comprehension. Understanding the story deeply and reasoning about events and characters are central to children's enjoyment and to comprehension skills needed for later reading. Preschoolers have capacities for inferential thinking, but little practice‐based instruction, except for asking questions, has resulted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Question asking is a starting point for students to generate inferences (McCrudden & McNamara, 2017). Research demonstrates that teaching students the importance of asking questions, how to ask questions, to answer their questions, and to evaluate the quality of their questions leads to improved comprehension (Cohen, 1983; Davey & McBride, 1986). For example, Davey and McBride (1986) found that students who were given question asking training wrote higher quality questions, scored higher on both literal and inference comprehension questions, and had better metacomprehension accuracy compared to students in comparison conditions.…”
Section: Comprehension Strategy Instruction In Istart‐earlymentioning
confidence: 99%
“…Question asking is a starting point for students to generate inferences (McCrudden & McNamara, 2017). Research demonstrates that teaching students the importance of asking questions, how to ask questions, to answer their questions, and to evaluate the quality of their questions leads to improved comprehension (Cohen, 1983; Davey & McBride, 1986). For example, Davey and McBride (1986) found that students who were given question asking training wrote higher quality questions, scored higher on both literal and inference comprehension questions, and had better metacomprehension accuracy compared to students in comparison conditions.…”
Section: Comprehension Strategy Instruction In Istart‐earlymentioning
confidence: 99%
“…Active reading can include highlighting, annotation, and note‐taking (Soto et al, 2019). It can also include asking questions whilst reading—not answering them (Cohen, 1983; Singer, 1978). These approaches to reading and study can increase retention, comprehension, and engagement with scientific ideas (Roy et al, 2021; Toste et al, 2020; Toyokawa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%